(3eLGRGJ OhGFQ GdSehJ aj GdCSWQdGHs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3PcQJ (B- (3GYRc Gddg (B- (3Cf WQbkG ef GdMSGH ai eYQaI eLGR OhGFQ GdSehJ ai GdGSWQdGH Ydi GdGab s
(3BNQgG (B:s
(3Hd gh dc bGfhf JbjS Hg SGFQ eG jbY Edjc ef CeKGdgG hJSJfHW HgG eYQaI UMjMgG ef SbjgeG acf Hg SYjOkG JeJ Hg GdQSGdI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B79(3H (B- (3U(B83(3Hs
(3cJHJ Hbde eged GdfbW CMjGfGs
(3HgG fXGe GdJYbjHIs
(3gPg GdeNWhW YHGQI Yf QSGdI HYK HgG GdeDda Edi CHj GdQjMGf eMeO Hf CMeO GdHjQhfi J SfI (B440 (3g`s
(3HgG CTcGd gfOSjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3Gdadcs